A Comparative Study on Factors Influencing Housing Loan Borrowers of Public and Private Sector Banks in Uthamapalayam Taluk - Hasanbanu, S.; Shree, U. Jeya (Indian Journal of Marketing, 2006)
Every human being aspires of his own house to live in. After food and clothing, housing is the third most important human requirement. On an average a person spends almost two-thirds of his life in a house which his sanctuary in his old age. Adequate housing is therefore a fundamental need of human beings and an essential pre-requisite for physical, intellectual and mental development. Blessed are those who live in their own house and fortunate are those who have the money to buy one. But all are not privileged to buy a house of their own. For many such less privileged, buying a house has become possible in modern times through housing loans.